Achieving nanosecond time resolution with a two-dimensional X-ray detector - Chushkin, Yuriy; Correa, Jonathan; Ignatenko, Alexandr; Pennicard, David; Lange, Sabine; Fridman, Sergei; Karl, Sebastian; Senfftleben, Björn; Lehmkühler, Felix; Westermeier, Fabian; Graafsma, Heinz; Cammarata, Marco (Journal of Synchrotron Radiation, 2025)
The fastest pixel array X-ray detectors can record images with nanosecond resolution. This is accomplished by storing only a few images in in-pixel memory cells. In this study, we demonstrate nanosecond resolution over a large number of images by operating a prototype detector in an event driven mode. The performance of this mode is tested by measuring the Brownian dynamics of colloidal nanoparticles. We can achieve sub-100 ns time resolution and overcome the pixel dead time by applying a cross-correlation analysis of the neighboring pixels. The approach used in this work can be extended to study time-resolved fast processes with diffraction, scattering or imaging techniques.
CRIS-Team Scopus Importer:2025-09-26
Keywords: photon science; Timepix4; X-ray detector; XPCS